The Song of Songs and the Eros of God: A Study in Biblical Intertextuality - Kingsmill, Edmée (Oxford Theological Monographs, 2009)
A close biblical study that re-examines the Hebrew text of the Song of Songs and considers its mystical meaning. Kingsmill seeks to demonstrate that a careful network of intertextual allusions has been deliberately used by the writer of the Song to refer metaphorically to the love of God for his people.